2021
DOI: 10.1037/tra0000967
|View full text |Cite
|
Sign up to set email alerts
|

Coping and rumination as mediators in the development of reactive embitterment in the general population.

Abstract: Objective: Embitterment encapsulates reactive emotions such as worthlessness or helplessness after negative life events that contravene one’s basic beliefs. However, no psychological model of the development of persistent embitterment has yet been investigated. We examined mediating factors for reactive embitterment, focusing on cognitive processes, including coping and rumination, among young South Korean adults. Method: A total of 1,000 young adults aged 18–35 answered an online survey questionnaire measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Finally, while optimism appeared to be protective, maladaptive forms of coping, such as substance use and behavioral disengagement, were associated with an increased likelihood of having persistent distress, which is consistent with prior literature (Feder et al 2016 ; Feingold et al 2021 ; Løvstad et al 2020 ; Mazure et al 2000 ; Yoo et al 2020 ). Resilience-building interventions are one strategy that may help bolster optimism and promote adaptive coping during a crisis.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, while optimism appeared to be protective, maladaptive forms of coping, such as substance use and behavioral disengagement, were associated with an increased likelihood of having persistent distress, which is consistent with prior literature (Feder et al 2016 ; Feingold et al 2021 ; Løvstad et al 2020 ; Mazure et al 2000 ; Yoo et al 2020 ). Resilience-building interventions are one strategy that may help bolster optimism and promote adaptive coping during a crisis.…”
Section: Discussionsupporting
confidence: 88%
“…The most interesting finding of this study is that dysfunctional coping was positively associated with PTG, which was inconsistent with several previous studies. For example, Yoo et al (2021) found that maladaptive responses or avoidance coping (e.g. denial, behavioural disengagement, substance use) may increase the risk of reactive embitterment when people experience negative events.…”
Section: Discussionmentioning
confidence: 99%
“…A four-score Likert scale method was used in the scoring. In accordance with previous studies (Lloyd et al, 2019;Yoo et al, 2021), three Brief COPE subscales were created: problemfocused coping (i.e. active coping, instrumental support and planning), emotion-focused coping (i.e.…”
Section: Coping Behaviourmentioning
confidence: 99%